Enterotoxigenic gene profiles of Bacillus cereus and Bacillus megaterium isolates recovered from honey - Alippi, Adriana Mónica (2010)
One hundred and thirty two Bacillus cereus and 52 Bacillus megaterium isolates from honeys were evaluated for the presence of genes encoding enterotoxin HBL, enterotoxin-T, cytotoxin K and the NHE complex, respectively. The relationship between hemolytic and coagulase activity and its correlation with the presence of the four mentioned enterotoxins was determined by principal component analysis (PCA). PCA in B. cereus revealed a positive correlation among free coagulase, hemolysis and the presence of genes hblA, hblB, hblC, hblD (HBL complex) and bceT (enterotoxin-T), but no correlation with the clumping factor (bound coagulase) and the presence of sequences of the NHE complex. On the other hand, PCA in B. megaterium showed a high positive correlation between coagulase (bound and free) and the haemolytic activity but no correlation in relation to the presence of genes of the HBL complex, cytotoxin K, enterotoxin T and the NHE complex. To our knowledge, this is the first report of the detection of cytotoxin K and of the NHE complex genes in B. megaterium. The relationship between the coagulase activity and the presence of virulence factors has not been described before in the genus Bacillus, being this work the first report of this correlation. Interestingly, the presence of the cytK gene was almost independent of the presence of the rest of virulence factors herein analyzed both in B. cereus and B. megaterium populations. Our results suggest that honey could be a possible vehicle for foodborne illness due to the presence of toxigenic B. cereus and B. megaterium strains containing different virulence factors.